Implanting MnO into a three-dimensional carbon network as superior anode materials for lithium-ion batteries - Zheng Liu (Elsevier, 2021)
A three-dimensional MnO/C nanocomposite is fabricated through a simple route of immersion and subsequent calcination. The carbon content and morphology of the sample are adjusted by adjusting the calcination temperature. This material combines the excellent lithium storage performance of MnO and the good stability of carbon. Because MnO is embedded in the three-dimensional carbon networks, it can provide proper space to alleviate the volume effect during discharging and charging. The unique architecture and large surface area enable the composites to exhibit remarkable lithium storage properties with outstanding rate performance, high reversible capacity, and cycle life. The optimized sample (MnO/C-750) has excellent performance of 1067.95 mAh g−1 at 0.2 A g−1 over 200 cycles and 722.32 mAh g−1 at 1 A g−1 over 600 cycles.